Perancangan Desain Kemasan sebagai Upaya Rebranding Promosi Produk UMKM - Yakob, Freddy; Kartika, Tipri Rose; Akmalia, Nurul; Ardiani, Septia; Rahmayanti, Handika Dany (Kreator, 2024)
The packaging design process for SMEs is often not a primary priority. As a result, business owners frequently overlook the branding process. Therefore, the design of this packaging is necessary as an effort to rebrand their products to increase their recognition. This study employs a qualitative descriptive method, utilizing interviews and literature reviews. Through the processes of recopy, recolor, and relayout, a redesign is carried out for products that previously had existing designs. The results show that recopy effectively communicates the message, recolor enhances the product's visual appeal, and relayout gives the packaging a more premium appearance, enabling SMEs to elevate their market position. This packaging design process is not merely about changing the appearance but is also a message construction process through words, colors, and layouts that can leave a lasting impression on consumers' minds.